The occurrence of dental caries is associated with atherosclerosis (Clinics, 2013)
OBJECTIVE: Previous studies have suggested that marginal periodontitis is a risk factor for developing atherosclerosis. The objective of this study was to determine whether caries may also be associated with atherosclerosis. METHODS: The computed tomography data sets of 292 consecutive patients, 137 women and 155 men with a mean age of 54.1±17.3 years, were analyzed. Caries were quantified based on the number of decayed surfaces of all the teeth, and periodontitis was quantified on the basis of the horizontal bone loss in the jaw. The presence of chronic apical periodontitis (CAP) was assessed, and the aortic atherosclerotic burden was quantified using a calcium scoring method. RESULTS: The patients with